2011
DOI: 10.1080/13545701.2011.582028
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Life Satisfaction in the UK

Abstract: This contribution analyzes the variations in reported life satisfaction for men and women in the United Kingdom. While average levels of life satisfaction are similar for men and women, the variations in life satisfaction are more marked for women. Analyzing the British Household Panel Survey (BHPS) for 1996-2007, the paper finds that hours of paid work increase life satisfaction for both men and women, while housework hours are statistically significant only for retired men and women. Childcare (for children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 29 publications
7
46
1
Order By: Relevance
“…Much of the existing literature on subjective well-being is focused on personal characteristics, microeconomic, and macroeconomic factors (such as income, hours worked, inflation and unemployment) and social relationships (Argyle, 2003;Clark, Knabe, & Ratzel, 2010;Diener, Ng, Harter, & Arora, 2010;Diener & Suh, 2000;Dolan, Peasgood, & White, 2008;Easterlin, 2001;Frey & Stutzer, 2002;Kahneman, Diener, & Schwarz, 2003;Kenny & Kenny, 2006;Layard, 2006;Stutzer & Frey, 2010;Tella, MacCulloch, & Oswald, 2003). Studies in Western market economies find that while hours of paid employment increase both men's and women's subjective well-being (Della Giusta et al, 2011), employment is more central to men's rather than women's well-being (Argyle, 2003), as is job satisfaction (Della Giusta et al, 2011). There is little overall difference in the impact of being married on men's and women's subjective well-being but a bad marriage has a greater negative impact on women than on men (Myers, 2003) while caring for dependents negatively affects women's but not men's subjective well-being (Della Giusta et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…Much of the existing literature on subjective well-being is focused on personal characteristics, microeconomic, and macroeconomic factors (such as income, hours worked, inflation and unemployment) and social relationships (Argyle, 2003;Clark, Knabe, & Ratzel, 2010;Diener, Ng, Harter, & Arora, 2010;Diener & Suh, 2000;Dolan, Peasgood, & White, 2008;Easterlin, 2001;Frey & Stutzer, 2002;Kahneman, Diener, & Schwarz, 2003;Kenny & Kenny, 2006;Layard, 2006;Stutzer & Frey, 2010;Tella, MacCulloch, & Oswald, 2003). Studies in Western market economies find that while hours of paid employment increase both men's and women's subjective well-being (Della Giusta et al, 2011), employment is more central to men's rather than women's well-being (Argyle, 2003), as is job satisfaction (Della Giusta et al, 2011). There is little overall difference in the impact of being married on men's and women's subjective well-being but a bad marriage has a greater negative impact on women than on men (Myers, 2003) while caring for dependents negatively affects women's but not men's subjective well-being (Della Giusta et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 97%
“…While policy makers and society at large clearly need to engage with the lack of agency, from the individual woman's perspective, the lack of subjective well-being is an important problem. Therefore, for an individual, both objective and subjective evaluations matter as they reflect a holistic continuum from resources to the capability to use these resources and then onto well-being (Della Giusta, Jewell, & Kambhampati, 2011). Our research here focuses on one element of this continuum -subjective wellbeing.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies find that women are happier or more satisfied with their lives than men (Easterlin 2003;Blanchflower & Oswald 2004), others find no gender difference (Kahneman & Krueger 2006;Della Giusta et al 2011), and yet others find that women are less happy or less satisfied with their lives (Mroczek & Kolarz 1998). What seems to be more certain is that variation in reported wellbeing is higher amongst women (Della Giusta et al 2011), as they have a higher tendency than men to report both being very happy and very unhappy (Frey & Stutzer 2002). It has been suggested that the relationship between gender and subjective wellbeing is moderated by age, with subjective wellbeing rising for men and declining for women over the adult life cycle (Marcelli & Easterlin 2005).…”
Section: Subjective Wellbeingmentioning
confidence: 99%
“…In particular, Swiss women may gain more in happiness in expectation and right after a birth than Swiss men, but they may experience steeper drops the following years (Clark et al 2008). Part of the stronger dip may be due to a larger anticipation effect, but it may also be due to the fact that women are more socially isolated after childbirth, as they have often taken leave from the labour force and act as the primary caregiver, particularly when the child is young (Della Giusta et al 2011;Simon 1992).…”
Section: Family Events and Well-beingmentioning
confidence: 99%